New Paracoccidioides brasiliensis isolate reveals unexpected genomic variability in this human pathogen (2008)
ABSTRACT: By means of genealogical concordance phylogenetic species recognition (GCPSR), we have investigated coding and non-coding regions from various genes and the ITS sequences of 7 new and 14 known isolates of Paracoccidioides brasiliensis. Such isolates grouped within the three phylogenetic groups recently reported in the genus Paracoccidioides, with one single exception, i.e., Pb01, a strain that has been the subject of intense molecular studies for many years. This isolate clearly separates from all other Paracoccidioides isolates in phylogenetic analyses and greatly increases the genomic variation known in this genus.